Clinical Pharmacy Practice in Low and Middle-Income Countries; Special Focus on Nepal - Khadka, Sitaram; Khatri, Mahesh; Lamichhane, Sabitri; Dhakal, Sagar (Journal of Karnali Academy of Health Sciences, 2022)
The paradigm shift of pharmacy practice from the conventional compounding and dispensing role towards more advanced patient-centered care has a positive impact on the health care system. Not only has it rendered safe, appropriate, and cost-effective drug therapy, but it has also optimized the therapeutic outcome. Though there is optimal growth of clinical pharmacy practice in the developed world, incorporating these new models into action has become a challenge for low-and middle-income countries (LMICs) like Nepal. Notably, the existing pharmacy curriculum is not updated to meet the current healthcare needs. Currently, the job opportunities are limited to manufacturing roles in pharmaceutical industries and as dispensers in the community and retail pharmacies. Pharmacists and pharmacy practice have to evolve with the latest trends in demographics, epidemiology, societal factors, economy, and technological advances. It is high time that the policy-making bodies prepare and implement guidelines for strengthening clinical pharmacy practice in LMICs. The clinical pharmacy practice assures the rationalization of therapeutic outcomes with proper protocols, effort from the pharmacists, sound academic background and related training, and professional attitudes. This review sought to explore and expand the role of clinical pharmacists in healthcare settings, particularly in LMICs like Nepal.